Gentamicin-loaded polyvinyl alcohol/whey protein isolate/hydroxyapatite 3D composite scaffolds with drug delivery capability for bone tissue engineering applications - ŞAHİN, ALİ; GÜNDÜZ, OĞUZHAN (My University, 2022)
Bone defects caused by diseases such as bone diseases, tumours, and traumas negatively affect the lives of millions of people around the world. Bone tissue engineering offers a new approach to repairing bone defects. Here, a novel bioactive Polyvinyl alcohol (PVA)/ Whey protein isolate (WPI)/ Hydroxyapatite (HA) composite scaffolds with Gentamicin (GEN)-loaded at varying rates were successfully fabricated by 3D printing technology. The strong interaction between PVA, WPI, HA, and GEN were proved with Fourier transform infrared spectroscopy (FT-IR) and X-ray diffraction (XRD). When the scanning electron microscopy (SEM) images of the produced 3D composite scaffolds were evaluated, it can be said that 3D composite scaffolds with the desired porosity and structure for bone tissue engineering applications were obtained. The 3D PVA/WPI/HA/12GEN composite scaffold was fabricated excellently with its 675 μm pore size. Compression tests revealed that the 3D composite scaffold had a compressive strength of 1.28–1.22 MPa and strain of % 12.89–8.70 and thus met the mechanical desirables of human trabecular bone. Moreover, the compressive strength and strain values of the scaffolds were decreased slightly due to adding the GEN drug. According to the Differential scanning calorimetry (DSC) analysis, it was determined that the highly crystalline structure of PVA was disrupted by adding GEN to the composite scaffolds. It was also observed that the addition of GEN to the scaffold did not significantly affect the swelling and degradation behaviour, and the scaffolds degraded by approximately 55% on the 10th day. The scaffolds exhibited a controlled release profile up to 240 and 264 h and were released with the Korsmeyer-Peppas kinetic model according to the highest correlation number. Cell analysis revealed that biocompatible structures were produced, and osteoblasts formed filopodia extensions, resulting in healthy cell attachment. According to these results, 3D GEN-loaded PVA/WPI/HA composite scaffolds may be a promising innovation for bone defect repair in bone tissue engineering applications.
Keywords: Fizik; Astronomi ve Astrofizik; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Malzeme Bilimi; Uzay bilimi; MALZEME BİLİMİ, MULTIDISCIPLINARY; POLİMER BİLİMİ; KİMYA, ORGANİK; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); MATERIALS SCIENCE; CHEMISTRY; SPACE SCIENCE; MATERIALS SCIENCE, MULTIDISCIPLINARY; POLYMER SCIENCE; CHEMISTRY, ORGANIC; ASTRONOMY & ASTROPHYSICS; Genel Fizik ve Astronomi; Fizik Bilimleri; Polimerler ve Plastikler; Organik Kimya; Malzeme Kimyası; General Physics and Astronomy; Physical Sciences; Polymers and Plastics; Organic Chemistry; Materials Chemistry; Bone tissue engineering; 3D printing; Drug delivery; Gentamicin; Whey protein isolate; Hydroxyapatite; Polyvinyl alcohol